(untitled) (Indonesian Tourism Justice Review, 2024)
Tourism development in Indonesia has often come at the expense of indigenous land rights, with many communities facing displacement, environmental degradation, and loss of cultural heritage. This paper examines the impact of tourism development on indigenous land rights, focusing on the legal, social, and economic injustices that arise when indigenous lands are appropriated for tourism-related projects. Through case studies of tourism-driven land disputes in Bali, Sumatra, and Papua, the paper analyzes how the rapid growth of tourism has led to conflicts over land use, with many indigenous communities losing control over their ancestral territories. The study explores the legal frameworks governing land rights in Indonesia, highlighting gaps in protection for indigenous peoples and the challenges in implementing land reform policies. It also examines the role of local governments, national policies, and international organizations in addressing land dispossession and advocating for indigenous rights. The paper calls for the integration of land rights protections into tourism development policies and explores the potential for tourism to serve as a means of land reclamation and community empowerment when indigenous communities are actively involved in planning and decision-making.